3D numerical simulation of flap geometry optimization around the cylinder to collection of split up droplet. (23rd July 2021) - Alishah, Javad; Maddah, Soroush; Alinejad, Javad; Rostamiyan, Yasser
Abstract: The novelty of present work is surveying deformation, split up and remained volume of Newtonian droplet impact with diameter d = 1.6, 2 and 2.4 mm and the droplet velocity in v = 1 and 2 m s −1 around the solid cylinders without flap, with simple and angle flap. Three-dimensional simulation was based on the volume of fluid method with dynamic contact angle of droplet and validated with the experimental results of a droplet impact and spread over the edge surface. Comparison split up volume of droplet between cylinder without flap, with simple and angle flap, the least percentage of split up volume of droplet (16%) was on solid cylinder with angle flap for droplet d = 1.6 mm and v = 1 m s −1 . Also, the maximum remained volume of droplet (5.1781 × 10 −9 m 3 ) was on the solid cylinder with angle flap for droplet d = 2.4 mm and v = 1 m s −1 .